Kurâ Iwenu (a nossa pintura) : performance e resistência na pintura corporal Kurâ-Bakairi - Taukane, Isabel Teresa Cristina (2019)
The research in focus is carried out in the Bakairi Indigenous Land, located in the municipalities of Paranatinga and Planalto da Serra, in Mato Grosso. Unlike taking body paintings as artistic events in the field of fine arts, we consider it as an event of 'performance', whose interdisciplinary character permeates the fields of Anthropology, Fashion, Cultural Studies, Art, among others. However, even though body painting refers to mythical time, it is not static, it is all the time reinventing itself to continue existing, resisting the times, through hybridization processes, something particular and that justify the importance of research in this field. The aim of the research is to study the body painting of the Kurâ-Bakairi indigenous people as a skin garment. In order to understand how the practice resisted/resists the colonizing process to the present day, although initially the research was about graphics. Due to the extent of the theme, it was delimited that we would deal exclusively with body painting that has the graphics as a reason. The methodology used is participant and autoethnographic research using multiple research techniques such as: field research, interviews, research in bibliographic and ethnophotographic sources. The thesis explores body painting in contemporaneity, so that we can say that colonizing processes were not able to eliminate this cultural practice of the Kurâ-Bakairi people. We point out as the main reason for the permanence of this body graphic knowledge the cosmological relationships before colonization and its peculiar capacity to metamorphose. Thanks to this, not even in the face of the rupture of the way of existence, being and thinking, was able to eliminate the practices of body paintings. The thesis is structured in five chapters, initiated by this introduction and finalized with completion. In the second chapter, we approached indigenous graphics and paintings. In the third chapter, we deal with the origins of body paintings, geometric and graphic motifs and the processes of paint production and the transformations of the indigenous people. In the fourth chapter, we deal with performance and endurance from the performance of kurâbakairi body painting, the performactivities of the vest - body painting and nudity - and the performance of body painting as resistance.